2021
DOI: 10.3390/ijms22168846
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Biomarkers of Renal Cell Carcinoma for Liquid Biopsy Tests

Abstract: Renal cell carcinomas (RCC) account for 2–3% of the global cancer burden and are characterized by the highest mortality rate among all genitourinary cancers. However, excluding conventional imagining approaches, there are no reliable diagnostic and prognostic tools available for clinical use at present. Liquid biopsies, such as urine, serum, and plasma, contain a significant amount of tumor-derived nucleic acids, which may serve as non-invasive biomarkers that are particularly useful for early cancer detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 126 publications
(240 reference statements)
0
26
0
Order By: Relevance
“…Considering that various studies have reported other strategies for RCC identification (including imaging and epigenetic biomarkers), our results seem to offer the best sensitivity for RCC detection [ 9 , 54 ]. Indeed, the methodology we developed uses a lower initial sample volume [ 15 , 17 , 20 , 22 , 25 , 41 , 42 ], which is more cost-effective, and the procedure to obtain the sample is better tolerated by patients.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Considering that various studies have reported other strategies for RCC identification (including imaging and epigenetic biomarkers), our results seem to offer the best sensitivity for RCC detection [ 9 , 54 ]. Indeed, the methodology we developed uses a lower initial sample volume [ 15 , 17 , 20 , 22 , 25 , 41 , 42 ], which is more cost-effective, and the procedure to obtain the sample is better tolerated by patients.…”
Section: Discussionmentioning
confidence: 95%
“…The intense exploration of circulating epigenetic markers such as DNA methylation, miRNAs, and lncRNAs is well illustrated by the more that 60 articles published in this field since 2003 [ 9 ]. So far, 10 DNA methylation-based studies (e.g., using VHL, RASSF1A, P16, P14, RARB, TIMP3, GSTP1, APC ) for RCC detection have been published [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ] and only 33.33% of these had an RCC cohort with more than 50 patients [ 60 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations